RamB, a Novel Transcriptional Regulator of Genes Involved in Acetate Metabolism of Corynebacterium glutamicum - Gerstmeir, Robert (American Society for Microbiology, 2004)
The adaptation of Corynebacterium glutamicum to acetate as a carbon and energy source involves transcriptional regulation of the pta-ack operon coding for the acetate-activating enzymes phosphotransacetylase and acetate kinase and of the aceA and aceB genes coding for the glyoxylate cycle enzymes isocitrate lyase and malate synthase, respectively. Deletion and mutation analysis of the respective promoter regions led to the identification of highly conserved 13-bp motifs (AA/GAACTTTGCAAA) as cis-regulatory elements for expression of the pta-ack operon and the aceA and aceB genes. By use of DNA affinity chromatography, a 53-kDa protein specifically binding to the promoter/operator region of the pta-ack operon was purified. Mass spectrometry and peptide mass fingerprinting identified the protein as a putative transcriptional regulator (which was designated RamB). Purified His-tagged RamB protein was shown to bind specifically to both the pta-ack and the aceA/aceB promoter/operator regions. Directed deletion of the ramB gene in the genome of C. glutamicum resulted in mutant strain RG1. Whereas the wild type of C. glutamicum showed high-level specific activities of acetate kinase, phosphotransacetylase, isocitrate lyase, and malate synthase when grown on acetate and low-level specific activities when grown on glucose as sole carbon and energy sources, mutant RG1 showed high-level specific activities with all four enzymes irrespective of the substrate. Comparative transcriptional cat fusion experiments revealed that this deregulation takes place at the level of transcription. The results indicate that RamB is a negative transcriptional regulator of genes involved in acetate metabolism of C. glutamicum.